A Priori Estimation of the Solution for Mixed Problems with Integral Condition for Singular Parabolic Equations. (4th February 2014) - Almomani, Raid
Abstract : We prove a theorem in which we get a priori estimation of the solution for mixed problems with integral condition for singular parabolic equations. Mixed problems with nonlocal boundary conditions or with nonlocal initial conditions were studied in many works lately. Our result plays an important role in the theory of heat transmission, thermoelasticity, chemical engineering, underground water flow, and plasma physics.